JENIS-JENIS MAKNA DARI LIRIK-LIRIK LAGU TERLARIS BOYBAND VIXX - CLARENCIA, CHIQUITA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTÂ This research is entitled â€œJenis Makna dari Lirikâ€“Lirik Lagu Terlaris Oleh Boyband VIXXâ€. The aims of the research are to identify the types of meaning in the song lyrics, to classify the types of meaning and to analyze the meaning contained in the hit song lyrics by VIXX boy band.Â Â Â Â Â Â Â Â Â Â Â  This research used descriptive method. In collecting the data, the writer focused on identifying the words and phrases that contain the seven types of meaning based on theÂ  theory of Leech (1981) that divides the meaning into seven types, namely; conceptual meaning, connotative meaning, affective meaning, reflected meaning, collocative meaning, social meaning and thematic meaning. The writer then identifies and analyzes the part which contains the seven types of meaning respectively.Â Â Â Â Â Â Â Â Â Â Â  The results of this research show that the hit song lyrics of VIXX boyband have only 6 types of meaning. They are 8 conceptual meanings, 13 connotative meanings, 5 affective meanings, 13 reflected meanings, 9 collocative meanings and 13 thematic meanings. Â Â Â Â Â Keywords: Types of Meaning, Hit Song Lyrics of VIXX Boyband, Phrases, Sentences